1988
DOI: 10.1161/01.cir.77.4.935
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of postischemic ventricular fibrillation late after right or left stellate ganglionectomy in dogs.

Abstract: To gain insight into the differences in antiarrhythmic potential of right vs left stellate ganglionectomy, 72 dogs were randomized to either unilateral stellectomy or second intercostal space thoracotomy and left circumflex coronary arteriovenous pedicle occlusion was performed, without vagotomy, a mean of 8 weeks later under anesthesia. The type and timing of ventricular ectopic beats, including both nonsustained and sustained ventricular tachycardia and ventricular fibrillation, were investigated. Several co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

1989
1989
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(23 citation statements)
references
References 69 publications
0
23
0
Order By: Relevance
“…In conscious dogs with prior anterior myocardial infarction, left stellectomy seemed to protect against ventricular fibrillation during acute myocardial ischemia (40). In an anesthetized dog model without prior myocardial infarction, either left or right stellectomy protected against death by ventricular fibrillation after coronary occlusion (32). Unilateral increases and decreases of sympathetic tone to the heart can induce an asynchronous wall motion pattern affecting cardiac function (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…In conscious dogs with prior anterior myocardial infarction, left stellectomy seemed to protect against ventricular fibrillation during acute myocardial ischemia (40). In an anesthetized dog model without prior myocardial infarction, either left or right stellectomy protected against death by ventricular fibrillation after coronary occlusion (32). Unilateral increases and decreases of sympathetic tone to the heart can induce an asynchronous wall motion pattern affecting cardiac function (38,39).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have shown that hypotension is a common phenomenon already during the early stages of acute coronary occlusion both in the experimental and clinical settings [18,23,24]. The background of early hypotension involves complex mechanisms.…”
Section: Hypotension During Acute Myocardial Ischaemiamentioning
confidence: 99%
“…17 The left cardiac sympathetic system is recognized as predominantly regulating arrhythmogenic potential, whereas the right-sided system primarily regulates heart rate. 18-20 Left sympathectomy is, therefore, usually the initial surgery of choice, although staged or concurrent right-sided sympathectomy also can be performed when the etiology of the ventricular arrhythmia is deemed to be more complex (a synergistic interaction between arrhythmogenic stimulation and heart rate, for example) or particularly sensitive to sympathetic stimulation. This differs from recommendations for ganglionic blockade, for which bilateral blockade absolutely is contraindicated because of concerns for fully eradicating sympathetic tone to the heart.…”
Section: Discussionmentioning
confidence: 99%